Coping strategies used by the nursing staff in caring for cancer patients and family - Pamela Karin Lazzaroto; Kátia Lilian Sedrez Celich; Silvia Silva de Souza; Marcela Martins Furlan de Léo; Tatiana Gaffuri da Silva; Leoni Terezinha Zenevicz (Universidade Federal de Santa Maria, 2018)
Aim: to identify the coping strategies used by nursing staff in caring for cancer patients and family in the hospital environment. Method: a descriptive exploratory study with a qualitative approach based on the reference of Lazarus and Folkman on coping. The research was developed with eight members of the nursing staff of a hospital oncology unit in the East of Santa Catarina, who responded to a semi-structured interview about their coping in the daily work in oncology. The information analysis occurred by means of thematic analysis. Results: The ones that pointed the emotion-focused coping were the following: escape-avoidance and positive reevaluation and coping focused on the problem: planned resolution, social support and self-control. Final Notes: the daily care in oncology awakens suffering, a situation that leads to the development of various forms of handling in order to face this reality and promote adaptation and well-being.